Culture-Based Standard Methods for the Isolation of Campylobacter spp. in Food and Water - Neyaz Leena A.; Arafa Sara H.; Alsulami Fatimah S.; Ashi Hayat; Elbanna Khaled; Abulreesh Hussein H. (Polish Journal of Microbiology)
Campylobacter spp. is a major source of global gastrointestinal infections. Their enteric infections are linked to the consumption of undercooked poultry products, contaminated milk and water, and the handling of wild animals and birds. The detection of Campylobacter spp. in water and food samples mainly depends on culture-based techniques. Public Health England (PHE), the U.S. Food and Drug Administration (FDA), and the International Standard Organization (ISO) have standardized Campylobacter spp. isolation and enumeration procedures for food and water samples, which involve the usage of selective agar media and enrichment broth. Different types of selective plating and enrichment media have been prepared for Campylobacter spp. detection and assessment during regular food surveillance and food poisoning. To date, culture media remains the standard option for microbiological food analysis and has been approved by the U.S. Environmental Protection Agency (US EPA), Food and Agriculture Organization (FAO), and World Health Organization (WHO). This review discusses the standard microbiological protocols for Campylobacter spp. isolation and enumeration in food and water and evaluates detection media (pre-enrichment, selective enrichment, and selective plating) for their rational applications. Moreover, it also elaborates on the advantages and disadvantages of recent chromogenic culture media in Campylobacter spp.-oriented food surveillance. This review also highlights the challenges of culture-based techniques, future developments, and alternative methods for Campylobacter spp. detection in food and water samples.